A new biometric matching fingerprints system for personal authentication using R305 - Urooj Khan, Samra; Abbasi, Waseem; Mohd Nawi, Nazri; Khan, Zoya; Naqeeb Khan, Sundas; ur-Rahman, Atta- (Excelligent Academia, 2020)
Now days, security is the main concerning research area for public and private sectors. Security become a major issue in many of our daily life places such as offices, libraries, hospitals, houses, laboratories, educational institutes, military areas etc where in these places, our privacy and confidentiality are very high. A number of methods used to solve this issue in different ways. One of the methods used for authentication of any individual to desired place entrance is door lock security system. This paper implements R305 which is a fingerprint based system design that that used security system for authentication on fingerprint process along its unique patterns. Furthermore, Arduino UNO device is used for this physical security by fingerprints. This project will become a prototype of biometric system since each fingerprint has a unique pattern and cannot be stolen, shared or any type of rudeness. The effectiveness of the proposed system has been verified and the results show that 95% accuracy with matching results on selected datasets.